Effect of density of the whitefly predator Delphastus pusillus (Le Conte) (Coleoptera: Coccinellidae) on its searching efficiency - GARCÍA-GONZÁLEZ, JAVIER; BENÍTEZ-S., EDGAR RICARDO; BENÍTEZ-S., EDGAR RICARDO; LÓPEZ-ÁVILA, ARISTÓBULO (Revista Colombiana de Entomología, 2006)
The effect of density of the predator Delphastus pusillus (Le Conte), defined by the components of aggregation and interference, was determined in relation to searching efficiency of its prey, the whitefly Trialeurodes vaporariorum (Westwood). To determine aggregation behavior, ten adults of D. pusillus were put together with five prey densities, 8, 16, 32, 64 and 128 third instar nymphs. A 5 x 5 latin square design was used, where the estimated variables were number of predators present in each prey patch, time spent per predator on each prey patch, prey consumed and eggs laid per predator in each prey patch. The aggregation coefficient µ was estimated from these variables. To determine interference behavior five densities of the adult predator, 1, 2, 4, 6 and 8, were evaluated on one prey density, 128 third instar nymphs. Each predator density was put with the prey in different experimental arenas. The statistical model used was a completely randomized design with five treatments and four replications. The number of predators present in the prey patch, time spent per predator in each prey patch, number of encounters between conspecifics, time spent in each encounter, quantity of prey consumed and number of eggs laid was measured. The model of searching efficiency and the interference coefficient ( ) were estimated. The results obtained for each analyzed variable are presented and the models of aggregation and interference for D. pusillus are estimated.